Α-Globin Genotypes Associated with Hb H Disease: A Report from Oman and a Review of the Literature from the Eastern Mediterranean Region. (2nd January 2020) - Al-Riyami, Arwa Z.; Daar, Shahina; Kindi, Salam Al; Madhani, Ali Al; Wali, Yasser; Rawahi, Mohammed Al; Zadjali, Shoaib Al
Abstract: α-Thalassemia (α-thal) is the most common autosomal recessive hemoglobinopathy. There is a vast diversity and geographical variability in underlying genotypes in Hb H (β4) patients. Herein, we describe the genotypes found in the largest report of Omani Hb H patients. Moreover, we reviewed and summarized the literature published from the Eastern Mediterranean region. A retrospective review of all genetically confirmed Hb H disease patients diagnosed between 2007 and 2017 at Sultan Qaboos University Hospital, Muscat, Oman, was performed. Hematological parameters and clinical presentations were assessed. Both α-globin genes were screened for deletional and nondeletional mutations using a stepwise diagnostic strategy as described before. A total of 52 patients (27 females and 25 males) with a mean age of 20.6 years (range 0.23–80.0) were molecularly confirmed to carry Hb H disease. The patients had a hemoglobin (Hb) level of 9.3 g/dL (range 5.7–13.0) and mean corpuscular volume (MCV) of 58.4 fL (range 48.2–82.1). A total of eight genotype combinations were identified, with α2 polyadenylation signal mutation (polyA1) (AATAA A >AATAA G (α PA1 α/α PA1 α), often cited as α T-Saudi α/α T-Saudi α, being the most common (53.8%) followed by –α 3.7 /– – MED I (28.8%). Our cohort also included patients with combinations of α PA1 with other Hb variants: α PA1 α/α PA1 α with Hb S ( HBB : c.20A>T) trait ( n  = 2), –α 3.7 /α PA1 α ( n  = 2) and α codon 19 α ( HBA2 : c.56delG)/α PA1 α ( n  = 1). Nondeletional Hb H disease due to the α PA1 mutation is the most common in Omanis. Molecular diagnosis is necessary for accurate confirmation of the diagnosis of α-thal, determination of underlying genotypes, follow-up and counseling.